TRADE COMPETITIVENESS OF INDONESIAN COCOA BEAN EXPORTS TO MAIN EXPORT DESTINATION COUNTRIES - Liskawati Sihaloho; Rahmanta; Sri Fajar Ayu (CV. Radja Publika, 2024)
The development of Indonesian cocoa bean exports before implementation of cocoa bean export duty policy showed that Indonesia was known as the third largest cocoa exporter in the world. However, on the one hand, the export volume of cocoa beans causes its domestic availability to fluctuate. This research aims to analyze the competitiveness of Indonesian cocoa beans, and analyze the factors that influence Indonesian cocoa bean exports in five main destination countries. The methods used in this research are Herfindahl Index (HI), Revealed Comparative Advantage (RCA), Export Product Dynamic (EPD), Trade Specialization (ISP) and Panel Data Regression. HI test results show an oligopoly market structure. RCA results are competitive (RCA > 1). EPD test results showed that Indonesian cocoa beans were in the Retreat position in USA, Singapore, India and Belgium except for Malaysia which was in the Lost Opportunity. The ISP results for Indonesian cocoa beans in Singapore, India and Belgium are at the maturity stage, while Malaysia and USA are at the growth stage. The research results show that export price of cocoa beans, the exchange rate, has a positive, while GDP per Capita has a negative and significant effect on the decline in the volume of Indonesian cocoa bean exports.